The role of biased calcium-sensing receptor signalling in urinary calcium excretion and kidney stone disease - Goldsworthy, Michelle (Journal of the Nuffield Department of Surgical Sciences, 2021)
Michelle Goldsworthy1,2, Asha Bayliss2, Anna Gluck2, Akira Wiberg3, Benjamin Turney1, Dominic Furniss3, Rajesh Thakker2, Sarah Howles1,2 1Nuffield Department of Surgical Sciences, University of Oxford, United Kingdom. 2Academic Endocrine Unit, Radcliffe Department of Medicine, University of Oxford, United Kingdom. 3Nuffield Department of Orthopaedics, Rheumatology and Musculoskeletal Sciences, University of Oxford, United Kingdom. Nephrolithiasis is a major health burden with a poorly understood pathogenesis. We conducted a genome-wide association study in British and Japanese populations identifying twenty nephrolithiasis-associated loci. Mutations in the calcium-sensing receptor (CaSR) cause disorders of calcium homeostasis and five identified loci (DGKD, DGKH, WDR72, GPIC1 and BCR) were predicted to influence CaSR-signalling. In a validation population, we demonstrated that genotype at the DGKD-associated locus correlated with urinary calcium excretion but not serum calcium concentration. In vitro studies demonstrated that knockdown and overexpression of DGKD resulted in biased CaSR-signalling. Thus, treatment of CaSR-expressing HEK cells with DGKD-targeted siRNA (DGKD-KD), resulted in decreased MAPK responses to alterations in extracellular calcium concentration [Ca2+]e, as assessed by SRE-reporter and ERK-phosphorylation (pERK) assays, when compared to cells treated with scrambled siRNA (WT) but without alteration in intracellular calcium responses [Ca2+]i as assessed by NFAT-reporter and Fluo-4 calcium assays (SRE maximal response DGKD-KD =5.28 fold change vs. WT=7.20 p=0.0065, pERK maximal response DGKD-KD=24.77, vs. WT= 39.46 fold change, p=0.0056). Conversely, DGKD overexpression (DGKD-OE) increased MAPK responses but suppressed [Ca2+]i responses to alterations in [Ca2+]e (SRE maximal response DGKD-OE =14.13 fold change vs. WT=9.06 fold change, p=0.01; NFAT maximal response DGKDOE= 13.67 fold change vs WT=59.16 fold change, p=0.0001). Our results demonstrate that alterations in DGKD expression cause biased CaSR-signalling. This biased signalling may provide an explanation for the correlation of genotype at the DGKDassociated locus with urinary calcium excretion but not serum calcium concentration. Our findings suggest that biased CaSR-signalling may be a common cause of nephrolithiasis.